Potentiation of natural killer cells to overcome cancer resistance to NK cell-based therapy and to enhance antibody-based immunotherapy - Fantini, Massimo; Arlen, Philip Martin; Tsang, Kwong Yok (Frontiers in Immunology, 2023)
NK cells are cellular components of the innate immune system that can recognize and suppress the proliferation of cancer cells. NK cells can eliminate cancer cells through direct lysis, by secreting perforin and granzymes, or through antibody-dependent cell-mediated cytotoxicity (ADCC). ADCC involves the binding of the Fc gamma receptor IIIa (CD16) present on NK cells to the constant region of an antibody already bound to cancer cells. Cancer cells use several mechanisms to evade anti-tumor activity of NK cells, including the accumulation of inhibitory cytokines, recruitment and expansion of immune suppressor cells such as myeloid-derived suppressor cells (MDSCs) and regulatory T cells (Tregs), modulation of ligands for NK receptors. Several strategies have been developed to enhance the anti-tumor activity of NK cells with the goal of overcoming cancer cells resistance to NK cells. The three main strategies to engineer and boost NK cells cytotoxicity include boosting NK cells with modulatory cytokines, adoptive NK cell therapy, and the employment of engineered NK cells to enhance antibody-based immunotherapy. Although the first two strategies improved the efficacy of NK cell-based therapy, there are still some limitations, including immune-related adverse events, induction of immune-suppressive cells and further cancer resistance to NK killing. One strategy to overcome these issues is the combination of monoclonal antibodies (mAbs) that mediate ADCC and engineered NK cells with potentiated anti-cancer activity. The advantage of using mAbs with ADCC activity is that they can activate NK cells, but also favor the accumulation of immune effector cells to the tumor microenvironment (TME). Several clinical trials reported that combining engineered NK cells with mAbs with ADCC activity can result in a superior clinical response compared to mAbs alone. Next generation of clinical trials employing engineered NK cells with mAbs with higher affinity for CD16 expressed on NK cells will provide more effective and higher-quality treatments to cancer patients.